2009
DOI: 10.1080/15389580903179901
|View full text |Cite
|
Sign up to set email alerts
|

Useful Field of View as a Reliable Screening Measure of Driving Performance in People With Parkinson's Disease: Results of a Pilot Study

Abstract: In this pilot study among PD patients, the UFOV may be a superior screening measure (compared to other measures of disease, cognition, and vision) for predicting on-road driving performance but its rigor must be verified in a larger sample of people with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 22 publications
5
63
0
Order By: Relevance
“…From the 12 Class II studies, 11 studies found that drivers with PD had significantly worse driving performance (p , 0.05) than healthy controls. 5,7,8,[10][11][12][13][15][16][17]25 No definitive conclusions could be made for one study as a control group was not included for on-road driving. 30 Although most drivers with PD were considered safe to drive, deficits that may affect driving were apparent even in the early stages of PD.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…From the 12 Class II studies, 11 studies found that drivers with PD had significantly worse driving performance (p , 0.05) than healthy controls. 5,7,8,[10][11][12][13][15][16][17]25 No definitive conclusions could be made for one study as a control group was not included for on-road driving. 30 Although most drivers with PD were considered safe to drive, deficits that may affect driving were apparent even in the early stages of PD.…”
mentioning
confidence: 99%
“…30 Although most drivers with PD were considered safe to drive, deficits that may affect driving were apparent even in the early stages of PD. There were 6 studies that found a clinical battery predicted driving performance 5,10,12,13,17,30 while one study did not. 9 Variables that predicted driving performance also differed across studies, as shown in However, based on 2 Class II studies, 5,17 UPDRS motor scores during the practically defined "off" period were concluded to be probably predictive of driving performance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence has shown that UFOV performance predicts driving competence (Owsley et al 1998), vehicle crashes , Owsley et al 1998, and driver safety (Clay et al 2005). This evidence, and the fact that UFOV can be administered without specialist training in a short amount of time (Classen et al 2009), has led to suggestions that UFOV may be suitable as a tool to quickly and reliably identify at-risk drivers (Bédard et al 2008). This suggested predictive nature of UFOV is likely due to its hypothesised reliance on both visual sensory abilities and higher order attentional skills (Owsley, 1994).…”
Section: Introductionmentioning
confidence: 99%